Role of Internal Communication in Enhancing Employee Engagement in the Nigeria Customs Service: A Two-Way Symmetrical Approach - Abdullahi Aliyu Maiwada (Feedback International Journal of Communication, 2025)
In today’s dynamic organisational landscape, strategic internal communication has become a crucial driver of employee engagement and performance. Traditional top-down communication methods are increasingly being replaced by integrative approaches that align employee behaviour with organisational goals. This shift is particularly significant in paramilitary organisations, where hierarchical structures and rigid protocols often hinder transparent and inclusive communication. This study employs a descriptive research method, drawing on secondary sources such as literature, media reports, official documents, and online resources relevant to internal communication and employee engagement within the Nigeria Customs Service. Grounded in the Two-Way Symmetrical Theory of Public Relations, which emphasises reciprocal communication and mutual understanding between employees and leadership, this paper examines the unique communication challenges within the Service. These challenges are shaped by the organisation’s diverse roles in revenue generation, trade facilitation, and law enforcement. The findings indicate that effective internal communication—supported by structured feedback mechanisms and transparency—enhances employee participation, satisfaction, and overall job performance. The study concludes that strategic internal communication not only mitigates operational complexities but also strengthens organisational cohesion, discipline, and shared values, all of which are essential for achieving institutional objectives.